Multi-criteria decision-making using game theory technique with application to oil production and price - Muhammad Akram Ramadhan, Ibrahim (2024)
Numerous studies have integrated game theory techniques with multi-criteria decisionmaking (MCDM) methods to address real-world problems. This research offers a thorough examination of the hybrid approach combining game theory techniques and MCDM methods. This thesis addresses three significant problems. The first problem identified in this research is the need to refine the trade-off ranking (TOR) method to better accommodate scenarios involving redundant extreme solutions. Redundant extreme solutions can arise in situations where the TOR method fails to effectively discriminate between multiple optimal solutions that do not significantly differ in their trade-off levels. The second problem is the multi-Nash equilibria selection, which fails to determine which Nash equilibrium (NE) is superior among multiple Nash equilibria. When multiple Nash equilibria exist, traditional approaches do not provide guidance on which equilibrium should be chosen. The third problem is the lack of research integrating game theory and MCDM methods to study trends in oil production and price. To address these problems, this research proposes refinements to the TOR method to better handle scenarios involving redundant extreme solutions, thereby enhancing decision-making efficiency. Later, a specific focus is given to the Shapley trade-off ranking method (STOR), a hybrid game theory technique and MCDM method. There is a discernible gap in the literature regarding the application of game theory technique and MCDM method to address issues related to oil production and price. The overarching goal of this research is to propose a ranked list of optimal oil production strategies, considering various political and economic criteria, in response to fluctuating oil prices. By exploring this intersection of game theory and MCDM in the context of oil-related challenges, this study aims to contribute valuable insights for addressing the intricate dynamics of the oil industry in the face of contemporary global uncertainties. This research uses the triangular fuzzy number to represent experts’ opinions by assessing the strategies, criteria and alternatives. A questionnaire is administered to collect information from decisionmakers. For the game theory computations, Gambit software is used to derive Nash equilibria. Shapley values are calculated using Microsoft Excel for characteristic functions and R software for Shapley value computation. The TOR and TOPSIS methods are thoroughly executed with Microsoft Excel. To evaluate the robustness of the decisionmaking process, the S-TOR method has been systematically compared with the TOPSIS method. The result suggests the ranking of the Nash equilibrium studied using the proposed method where the best strategy for Malaysia is to increase oil production while the best strategy for Organization of the Petroleum Exporting Countries (OPEC) is to maintain its oil production to stabilize the oil price. Future developments for the fuzzy and S-TOR approach include the addition of more players or an expansion of the criteria list, and the use of other fuzzy numbers to reflect an assessment of the DMs. Both practical applications and scholarly knowledge are increased by this research. One advantage of oil production and price analysis is the ability to plan optimal amounts of oil output to assist in avoiding oversupply issues